2007
DOI: 10.2533/chimia.2007.155
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Properties from Atomistic Simulations and Density Functional Theory

Abstract: Marcus theory of electron transfer is the quintessential example of a successful theory in physical chemistry. In this paper, we describe the theoretical approach we have adopted to compute key parameters in Marcus theory. In our method, based on molecular dynamics simulations and density functional theory, the redox center and its environment are treated at the same level of theory. Such a detailed atomistic model describes specific solvent-solute interactions, such as hydrogen bonding, explicitly. The quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…In previous work, we obtained satisfactory results for structure and dynamics of liquid acetonitrile with this basis set. [21] For the oxide, a recently developed procedure to derive molecularly optimized basis sets [34] has been employed to derive basis sets for Titanium and Oxygen. Using 5 primitives, basis sets of double-ζ quality have been optimized on small Ti-O compounds.…”
Section: Computational Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we obtained satisfactory results for structure and dynamics of liquid acetonitrile with this basis set. [21] For the oxide, a recently developed procedure to derive molecularly optimized basis sets [34] has been employed to derive basis sets for Titanium and Oxygen. Using 5 primitives, basis sets of double-ζ quality have been optimized on small Ti-O compounds.…”
Section: Computational Setupmentioning
confidence: 99%
“…In some of our previous work, we have shown that DFT based simulations using an atomistic representation of the solvent can capture these effects rather well, allowing for quantitative agreement with experiment for differences in redox potentials and solvent reorganization energies, even for large systems such as proteins. [19,20,21,22] In this work, we wish to focus on the solid/liquid interface that is most relevant in DSSC, namely the anatase(101)/acetonitrile interface. Indeed, anatase nanoparticles expose several crystal surfaces to the solvent, but anatase(101) is the dominant structure.…”
Section: Introductionmentioning
confidence: 99%
“…Many earlier reports of l i seem to be overestimated due to the neglect of these effects. 28 The outer-sphere solvent contribution l s can be estimated using MD simulations, [29][30][31][32] and the topics that were discussed previously include l s in a heterogeneous molecular environment 33 and the effect of the structural relaxation rate on the effective magnitude and the applicability of l s . 34 However, l s is sensitive to the force field used, and it is in particular non-polarizable force fields that tend to overestimate l s drastically as they neglect the fast component of dielectric response.…”
Section: Introductionmentioning
confidence: 99%
“…A rather accurate estimation of these parameters is required because of their appearance in the argument of an exponential, and the RE is particularly challenging to determine. It can be decomposed into two parts: the inner sphere RE l i , which is also sensitive to quantum effects [23], and the solvent contribution to the outer sphere RE l s , which can be calculated with classical MD simulations [24][25][26][27]; the effects of several structural and dynamic factors on l s have been discussed previously [28,29].…”
Section: Introductionmentioning
confidence: 99%